DOLAMA study: Effectiveness, safety and pharmacoeconomic analysis of dual therapy with dolutegravir and lamivudine in virologically suppressed HIV-1 patients. Issue 32 (August 2019) - Hidalgo-Tenorio, Carmen; Cortés, Luis López; Gutiérrez, Alicia; Santos, Jesús; Omar, Mohamed; Gálvez, Carmen; Sequera, Sergio; Jesús, Samantha Eisabeth De; Téllez, Franciso; Fernández, Elisa; García, Coral; Pasquau, Juan
Abstract : Abstract: Dolutegravir (DTG) has shown effectiveness in combination with rilpivirine in with experience of antiretroviral therapy (ART) and with 3TC in naïve patients (GEMINI trial). The main objectives of this real-life study were to analyze the effectiveness and safety of 3TC plus DTG in virologically suppressed HIV-1 patients and to conduct a pharmacoeconomic analysis. We conducted an observational, retrospective and multicenter study of HIV+ patients pretreated for at least 6 months with ART that was then simplified to 3TC + DTG for any reason. We gathered data on viral loads (VLs) during exposure to the DT, calculating the rate with VL < 50 copies/mL at week 48, and on associated adverse effects. The 177 HIV+ patients were collected, 77.4% male, with average age of 48.5 years and mean count of 252.2cell/μL CD4+ nadir lymphocytes; 96.6% had VL < 50 copies/mL and 674 cells/μL CD4+ lymphocytes. Median time since HIV diagnosis was 15 years, and median ART duration was 13 years, and 34.5% of patients were on mono- or dual-therapy before the switch. At week 48, 82.4% of patients had VL < 50 cop/μL using an intention-to-treat (ITT) analysis, 89.6% according to mITT, and 96.7% according to Per-Protocol analysis. 3.3% patients had virological failure (VF). These effectiveness data and costs were compared with those for 2 reference triple therapies (DTG/ABC/3TC and EVG/cobi/FTC/TAF) in a cost minimization analysis, showing cost savings with administration of DTG+3TC (2741 [Euro sign]/year vs DTG/ABC/3TC and 4164 [Euro sign]/year vs EVG/cobi/FTC/TAF) and in a cost-effectiveness analysis, finding the DT to be the most cost-effective approach (ICER = −548 vs DTG/ABC/3TC and ICER = −4, 627[Euro sign] vs EVG/cobi/FTC/TAF) The combination of 3TC with DTG appears to be a safe and effective option for the simplification of ART in pretreated and virologically stable HIV-positive patients, being cost-effective and offering the same effectiveness as the triple therapy it replaces.